Synthesis of arylated chalcone derivatives via palladium cross-coupling reactions. Issue 8 (21st February 2018) - da Costa, Rafaela G.M.; Farias, Francisco R.L.; Back, Davi; Limberger, Jones
Graphical abstract: Highlights: A methodology to arylate α- and β-positions of chalcones olefin moiety is described. β-Arylchalcones are synthesized and isolated with E : Z ratios ≥ 96:4. The nature of chalcone aryl group can affect dramatically the Heck reactivity. α, β-Diarylchalcones are obtained via sequential bromination/Suzuki reaction. Abstract: A useful protocol for arylation of the olefin double bond of chalcones to afford tri- and tetra-substituted chalcone derivatives is reported. The protocol begins with the Heck reaction between chalcones and aryl iodides providing β-arylchalcones. This reaction tolerates various functional groups on both rings, as well as deactivated aryl iodides. The products are obtained in moderate to excellent yields and the ( E )-β-arylchalcones ( E : Z > 96:4) can be isolated via precipitation. Competitive Heck reactions pointed to a significant effect of ring one substituents on the reaction rate, while substituents on ring two have a much smaller effect. To access α, β-diarylchalcones, a sequential bromination-Suzuki cross coupling strategy was applied to the β-arylated compounds which afforded double arylated chalcone derivatives in 60–99% yield over two steps.